A comparison of plantarflexor musculotendon unit output between plyometric exercises and running. Issue 4 (April 2022) - Trowell, Danielle; Fox, Aaron; Saunders, Natalie; Vicenzino, Bill; Bonacci, Jason
Abstract: Objectives: Plyometric exercises are used to prevent and rehabilitate plantarflexor running injuries. To facilitate exercise programming, this study compared plantarflexor musculotendon output during running to plyometric exercises. Design: Experimental study with cross-over. Methods: Fourteen trained distance runners performed running, ankle bouncing, A-skips, bounding, and hurdle jumps. Three-dimensional motion capture and force plate data were collected and computational simulations used to calculate gastrocnemius lateralis and soleus musculotendon peak forces, strain, power generation and absorption, and total positive and negative work. Percentage difference and standardised mean differences were used to compare variables between plyometrics and running. Musculotendon units were classified as energy generators or absorbers according to their net mechanical work. Results: Both plantarflexors behaved as net energy generators during running. Plantarflexor peak force and power generation and absorption were lower in the A-skip and ankle bounce compared to running. Soleus behaved as a net energy absorber during hurdle jumps, with greater total negative work (16.5%; standardised mean difference 0.92) and higher peak strain (0.3%; standardised mean difference 0.28) during hurdle jumps than running. Gastrocnemius lateralis behaved as a net energy absorber during bounding, with greater total negative work (63.8%; standardised mean difference 0.81) and peak strain (0.4%; standardised mean difference 0.77) during bounding than running. Conclusions: The ankle bounce and A-skip may be appropriate exercises when runners desire lower plantarflexor loads than running. Hurdle jumps elicited high soleus loads but low gastrocnemius lateralis loads, highlighting the disparate function of the plantarflexors. Bounding demanded high plantarflexor musculotendon output and may be suitable when eccentric overload is desired.